Transitivity Process on Dendang of Randai in the Art Performance of Minangkabau Culture - Muhammad Egi Wirdiansyah; Zuindra Zuindra (Journal of English Language and Education, 2021)
This research aimed to explore the dendang of randai to be analyzed in perpective of Systemic Functional Linguistic (SFL) proposed by Halliday (2014). The researchers wanted the lyrics of dendang to be analized using a theory of  Halliday in the text of Randai itself. The researchers used four dendang lyrics namely oepning Dendang, Dendang Simarantang, Gurindam Indang Payakumbuh, Gurindam Bacarai Kasiah. The researchers analyzed dendang using the types of transitivity process as the linguistic approach. The researchers used the Systemic Functional Linguistics developed by M.A.K Halliday. The data collection applied in this research by using books, articles in some jourlnals, e-books and other resources. The results showed that there were 6 types of transitivity process in which 8 sentences of material process, 4 sentences of mental process, 7 sentences of relational process, 15 sentences of verbal process, 2 sentences of behavioral process, and 2 sentences of existential process. The most dominant type of transitivty process found in dendang is verbal process.